Oblicz wartość liczbową wyrazenia:
xkwadrat+x-1 dla x= -1
2(-x+4) dla x= -10
1-y+x dla x=2 i y=-1
4x -(x+6)+4 dla x=jedna trzecia
(xkwadrat+1)-(xkwadrat-2)+10 dla x=2,2
(a+4b)- (5+2a) -(3b -5) dla a=0,1 i b=0,2
(-a kwadrat +2ab -1)+(a kwadrat -4ab+5) dla a=jedna czwarta i b=2






















2

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-02T08:41:11+01:00
Oblicz wartość liczbową wyrażenia:
x²+x-1 dla x= -1
(-1)²+(-1)-1=1-1-1=-1

2(-x+4) dla x= -10
2(-(-10)+4)=2(10+4)=2*14=28

1-y+x dla x=2 i y=-1
1-(-1)+2=1+1+2=4

4x -(x+6)+4 dla x=⅓
4*⅓-(⅓+6)+4=4/3-⅓-6+4=1-2=-1

(x²+1)-(x²-2)+10 dla x=2,2
(2,2²+1)-(2,2²-2)+10=(4,84+1)-(4,84-2)+10=
5,84-2,84+10=13

(a+4b)- (5+2a) -(3b -5) dla a=0,1 i b=0,2
(0,1-4*0,2)-(5+2*0,1)-(3*0,2-5)=(0,1-0,8)-(5+0,2)-(0,6-5)=
-0,7-5,2+4,4=-1,5

(-a ² +2ab -1)+(a ² -4ab+5) dla a=¼ i b=2
((-¼)²+2*¼*2-1))+(¼²-4*¼*2+5)=
1/8+1-1+1/8-2+5=2/8+3=3 i 1/4
8 3 8
2010-02-02T08:53:49+01:00
X²+x-1 =(-1)²-1-1=1-1-1=-1
2(-x+4)=2(-(-10)+4)=20+8=28
1-y+x=1-(-1)+2=1+1+2=4
4x -(x+6)+4=4*1/3-(1/3+6)+4=4/3-6⅓+4=-1⅓
(x²+1)-(x²-2)+10 dla x=2,2
(2,2²+1)-(2,2²-2)+10=(4,84+1)-(4,84-2)+10=
5,84-2,84+10=13
(a+4b)- (5+2a) -(3b -5)=(0,1+4*0,2)-(5+2*0,1)-(3*0,2-5)=(0,1+0,8)-(5+0,2)-(0,6-5)=0,9-(5,2)-(-4,4)=0,9-5,2+4,4=0,1
(-a kwadrat +2ab -1)+(a kwadrat -4ab+5)=((-¼)² +2*¼*2-1)+((¼)²-4*1/4*2+5)=(1/8+1-1)+(1/8-8/4+5)=1/8+1/8-2+5=2/8-2+5=0,25-2+5=3,25


9 3 9